Integration of transport modes in the face of the Brazilian economic development (Research, Society and Development, 2019)
This article aims to compare the modalities of rail and waterway transportation with the road modal, through its characterization, in order to evaluate the efficiency of cargo transportation in Brazil. The methodology was based on a bibliographical analysis of materials in the academic environment (articles, dissertations, theses and magazines) in order to raise the strengths and points of improvement in the transport sector in Brazil, to the detriment of its high multimodal potential, reach the transport efficiency needed to maintain its economic development. Among the information obtained, it was evidenced that for decades the transposition of the Brazilian goods has been given by the predominant modal road, which in turn is saturated and limited. Due to the lack of federal government investments in infrastructure and logistics, the country is on the verge of stagnation in economic growth, as production becomes more expensive as a consequence of the high costs involved in its transportation, leaving the products at a competitive disadvantage in the national territory and in exports. In this way, the article shows that there is no one mode of transportation better than another, the transportation route becomes more appropriate according to its purpose.